2012
DOI: 10.1590/s1415-52732012000500004
|View full text |Cite
|
Sign up to set email alerts
|

Ingestão de cálcio e densidade mineral óssea em mulheres adultas intolerantes à lactose

Abstract: ObjetivoComparar a ingestão de cálcio e a densidade mineral óssea entre mulheres adultas portadoras de intolerância à lactose e suas congêneres não portadoras da doença. MétodosA amostra foi composta por 60 mulheres jovens adultas (de 20 a 40 anos), separadas em dois grupos: 30 diagnosticadas com intolerância à lactose e 30 saudáveis. A ingestão de cálcio foi avaliada por três autorregistros alimentares, e a densidade mineral óssea do colo do fêmur por absortometria radiológica de dupla energia. ResultadosAs d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Moreover, it was also not possible to determine whether a reduced calcium intake provoked a lower BMD in the LI group. However, similar studies appoint to this direction 6 . The results of the present study complement these findings and suggest that the regular practice of physical exercise alone is not able to reverse the deleterious effects of LI.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Moreover, it was also not possible to determine whether a reduced calcium intake provoked a lower BMD in the LI group. However, similar studies appoint to this direction 6 . The results of the present study complement these findings and suggest that the regular practice of physical exercise alone is not able to reverse the deleterious effects of LI.…”
Section: Discussionmentioning
confidence: 91%
“…There is a consensus that LI individuals with below-average BMD showed a reduction in calcium intake 5,27,28,[30][31][32] . When the absorption of calcium, an essential micronutrient, is insufficient to replenish daily losses, calcium is removed from bones contributing to a negative balance of bone remodeling and may predispose individuals to osteopenia and osteoporose 6,13,28 . Unfortunately, calcium intake was not measured in this study, but in a previous study with a very similar population 6 , it was demonstrated that calcium intake in LI women was nearly three times lower compared to intake of the control women.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations